1983
DOI: 10.1080/15298668391405265
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Bacteria, Endotoxin and Fungi in Dust in Poultry and Swine Confinement Buildings

Abstract: Airborne dust in swine and poultry confinements was analyzed to determine concentrations of total and gram-negative bacteria, total fungi, Aspergillus fumigatus and endotoxin. Airborne concentrations of total and gram-negative bacteria in swine and confinement units have been found to be as high as, or higher, than those found in other environments, such as wastewater treatment plants and cotton card rooms, where microbiologically contaminated organic dusts were present. Airborne endotoxin concentrations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(117 citation statements)
references
References 0 publications
5
109
2
1
Order By: Relevance
“…The concentrations of endotoxin found in this study are similar to concentrations found in previous investigations (Olenchock et al 1982;Clark et al 1983;Thelin et al 1984;Hagmar et al 1990;Lenhart et al 1990). In most of the facilities investigated, concentrations exceeded the 10 ng/m 3 value suggested as a threshold for airways inflammation (Rylander 1997).…”
Section: Discussionsupporting
confidence: 93%
“…The concentrations of endotoxin found in this study are similar to concentrations found in previous investigations (Olenchock et al 1982;Clark et al 1983;Thelin et al 1984;Hagmar et al 1990;Lenhart et al 1990). In most of the facilities investigated, concentrations exceeded the 10 ng/m 3 value suggested as a threshold for airways inflammation (Rylander 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Hen laying hens (Clark et al 1983). Endotoxin levels in the air from poultry houses (230-284 EU/m 3 ) were about 10 times lower than reported in other studies (Omland 2002;Radon et al 2002).…”
Section: Mouldsmentioning
confidence: 84%
“…Endotoxin, or lipopolysaccharide (LPS), a cell wall component of Gram-negative bacteria, is considered a common component of the organic dusts present in many occupational environments, such as textile mills, swine and poultry operations, and automobile manufacturing plants [2,13,27]. LPS has been considered a major causative agent in the chronic bronchitis seen among workers in these environments; clinical signs such as coughing, chest tightness, fever, shortness of breath, and wheezing have been reported [4,13,27].…”
Section: Introductionmentioning
confidence: 99%